An assessment of silvopastoral systems condition and their capacity to generate ecosystem services in the Colombian Amazon - Casanoves, Fernando; Ngo-Bieng, Marie Ange (Taylor and Francis, 2014)
Livestock production in the Colombian Amazonia is typically dual-purpose (meat and milk) based on silvopastoral systems. We aimed to assess how the ecological condition of these systems correspond to the ecosystem services they generate based on an assessment of farmers’ knowl-edge of the tree species. We evaluated 159 paddocks. We recorded 143 tree species from 37 families, with 22 species being most common (relative occurrence frequency = 57%). Based on tree species composition, we characterized four states of silvopastoral condition (hereon ‘pad-dock condition types’) using clustering techniques: (i) High structural complexity and highest tree species richness (HSCR); (ii) High species diversity and tall trees (HDTT); (iii) High species diversity and medium-sized trees (HDMT); (iv) Structurally simple with lowest species richness (SSLR). Tree species richness was significantly higher in HSCR (11.70 ± 1.47 per paddock), than in SSLR (2.86 ± 0.80). HDTT and HDMT had similar richness, with intermediate values (5.55 ± 0.82 and 6.38 ± 0.51, respectively). Farmers appreciate a number of ecosystem services provided by the silvopastoral system, but a limited number of tree species are valued. This indicates the need for additional biodiversity conservation measures in these landscapes, including measures to improve knowl edge about the value of tree species with few occurrences or low densities.